2022
DOI: 10.31235/osf.io/ah4ky
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strategies of Translating Word Formation in James Joyce’s Ulysses from English into Arabic

Abstract: The present study investigates strategies for translating word formation in Ulysses (1922) by James Joyce. The study also identifies the translation strategies used by an Arabic translator to render neologisms in the novel into the target language. The study draws on the Venuti model of translation. Applying the Venuti model to the translations of word formations into Arabic will test their adequacy. Different new words resulting from the word formation process were used in the selected data. The findings show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…These difficulties suggest that such jokes may be deemed untranslatable due to the potential loss of their intended humorous effect during the translation process. This aligns with the conclusions drawn by, Alharthi (2016), Mahdjoubi and Djafour (2015), and Saleh (2018). This conclusion is also partially supported by El-Yasin (1997), who concluded that Arabic cultural jokes pose minor problems when translated into English, whereas linguistic jokes are often untranslatable.…”
Section: Discussionsupporting
confidence: 92%
“…These difficulties suggest that such jokes may be deemed untranslatable due to the potential loss of their intended humorous effect during the translation process. This aligns with the conclusions drawn by, Alharthi (2016), Mahdjoubi and Djafour (2015), and Saleh (2018). This conclusion is also partially supported by El-Yasin (1997), who concluded that Arabic cultural jokes pose minor problems when translated into English, whereas linguistic jokes are often untranslatable.…”
Section: Discussionsupporting
confidence: 92%
“…These difficulties suggest that such jokes may be deemed untranslatable due to the potential loss of their intended humorous effect during the translation process. This aligns with the conclusions drawn by, Alharthi (2016), Mahdjoubi andDjafour (2015), andSaleh (2018). This conclusion is also partially supported by El-Yasin (1997), who concluded that Arabic cultural jokes pose minor problems when translated into English, whereas linguistic jokes are often untranslatable.…”
Section: Discussionsupporting
confidence: 92%
“…Debbas and Haider's (2020) study is an insightful exploration of the cultural constraints that arise in subtitling the American animated sitcom Family Guy into Arabic, which is a crucial factor to consider in the translation process. Alharthi's (2016) study is an indispensable addition to the field as it identifies the subtitling strategies employed by Arab translators to overcome technical, linguistic, and cultural issues in translating humor in Seinfeld. The study also uncovers the factors that may have influenced the subtitlers' decisions, which is critical to consider in subtitling and dubbing.…”
Section: Literature Reviewmentioning
confidence: 99%